A tool for the semantic annotation, validation and optimization of business process models. (11th January 2023) - Di Martino, Beniamino; Colucci Cante, Luigi; Esposito, Antonio; Graziano, Mariangela
Abstract: The adoption of the business process model notation for the description of internal workflows and procedures by both public administrations and private organizations is steadily growing, thanks to the simplicity of the standard and its consistent expressivity. However, the lack of semantic support from BPMN can pose important limitations to its efficient use, as ambiguities in task definitions and communications can lead to misinterpretations. Furthermore, there is the need to validate the BPMNs, to check their adherence to regulations, especially in public administration, and to verify their conformance to security and privacy constraints. In this work, we present SemPrAnn, a semantic annotation tool for BPMN that, exploiting domain ontologies and logical rules, provides the possibility to unambiguously identify concepts in workflows and to run inferential engines against them to enforce the rules. The manuscript presents the methodology applied for the implementation of the tool, the tool itself with its exposed functionalities, and a case study demonstrating its current capabilities.